Skills for success: Understanding routes to desistance. Issue 7 (3rd October 2019) - Bain, Andy
Abstract: Researchers and practitioners may argue that in order to reduce instances of reoffending behavior needs to be modified. The author contends that there is a good deal of work that needs to be done in recognizing the importance of enabling skills for employment, the so-called soft skills. These are often an expectation, but not a given. The article builds upon current knowledge and understanding, highlighting the significance of this skill-set in successful resettlement, providing evidence of how improving life-skills for people can be just as important as any formalized certification in supporting change in offending behavior.